Latin American Spanish in three months - Cisneros, Isabel; Messenger, Ana Marie; Rodriguez-Saona, Roberto (London Hugo's Language Books, 1998)
A Spanish-language course for beginners, with a book that explains grammar and cassettes to enhance speaking and listening skills.
At head of title: Hugo's simplified system.
"Simplified language course"--Cover.
Set includes Latin American Spanish in three months / Isabel Cisneros. London : Hugo's Language Books, 1998 ; Hugo Latin-American spanish cassette course. [London] : Hugo's Language Books, c1998 [4 sound cassettes] ; Audio language courses : instruction. London : Hugo's Language Books, [19--].
Keywords: Spanish language -- English. -- Textbooks for foreign speakers; Spanish language -- Provincialisms -- Latin America